High-stability multi-element hybrid structural adhesive for new energy lithium battery and preparation method of high-stability multi-element hybrid structural adhesive
By designing polyurethane components A and polyurethane components B, and adding pluripotent A, pluripotent B and dibutyltin dilaurate, a high stability multivariate hybrid structural glue was prepared, which solved the problems of fewer types of structural glues and insufficient stability in the prior art, and significantly improved the performance and safety of lithium batteries.
Patent Information
- Application Number
- CN202510336111.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
In the prior art, there are fewer types of structural glues used in lithium batteries, and it is difficult to prepare diversified hybrid structural glues with high stability, which affects the performance and safety of lithium batteries.
The preparation of multivariate hybrid structural glue is achieved by designing polyurethane components A and polyurethane components B, and adding multivariate A components, a multivariate B component and dibutyltin dilaurate. The structural glue consists of polyurethane component A, polyurethane component B, pluripotent A, pluripotent B and dibutyltin dilaurate.
It significantly improves the stability and durability of structural glue, enhances the bonding strength and sealing performance of lithium batteries, improves the overall stability and safety of the battery, and at the same time imparts flame retardant and antibacterial properties to structural glue.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyurethane structural adhesives, and in particular to a high-stability multi-component hybrid structural adhesive for new energy lithium batteries and a preparation method thereof. Background Art
[0002] With the rapid development of new energy technologies, lithium batteries, as key components for energy storage and conversion, have been widely used in electric vehicles, energy storage systems, portable electronic devices, etc. However, the performance and safety of lithium batteries depend largely on their internal structure and material selection. As an important component in the manufacture of lithium batteries, structural adhesives not only fix and seal battery components, but also directly affect the thermal stability, mechanical strength and electrochemical properties of the battery.
[0003] In recent years, multi-component hybrid structural adhesives have received extensive attention in the field of materials science due to their unique chemical structure and performance advantages. By hybridizing different types of polymers, inorganic fillers and functional additives, structural adhesives with excellent comprehensive performance can be prepared. However, there are relatively few types of structural adhesives used in lithium batteries in the prior art. Therefore, how to prepare multi-component hybrid structural adhesives with high stability so that they can be better used in the lithium battery industry has become a technical problem that needs to be urgently solved by technicians in this field. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-stability multi-component hybrid structural adhesive for new energy lithium batteries and a preparation method thereof, aiming to prepare a multi-component hybrid structural adhesive with high stability so that it can be better applied in the lithium battery industry.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high-stability multi-component hybrid structural adhesive for new energy lithium batteries, wherein the high-stability multi-component hybrid structural adhesive for new energy lithium batteries is composed of the following components: a polyurethane component A, a polyurethane component B, an enhanced component A, an enhanced component B, and dibutyltin dilaurate; The polyurethane component A is a hydroxyl-terminated prepolymer prepared with castor oil, polyester diol, polyether polyol, diphenylmethane diisocyanate and trimethylolpropane as main raw materials; The polyurethane B component is an isocyanate-terminated prepolymer prepared with castor oil and polymethylene polyphenyl polyisocyanate as main raw materials.
[0006] Furthermore, the preparation steps of the polyurethane component A are: Step 1, weigh 50-60g of castor oil, 100-120g of polyester diol and 50-60g of polyether polyol into a flask, and dehydrate under vacuum at a temperature of 120°C for 2h, and the obtained mixture is recorded as a mixed component; Step 2, cool the mixed components to 60°C and put them into a stirring kettle, then add 100-130g of diphenylmethane diisocyanate and heat to 80°C and mix and stir for 2h, then add 10-20g of trimethylolpropane, 1-5g of fumed silica and 20-40g of calcium carbonate powder, stir vigorously and evenly, then heat to 120°C and vacuum dehydrate for 2h, the result is recorded as the reaction component; Step 3: After cooling the reaction components to 40°C, add 20-40g of flame retardant plasticizer, 30-50g of flame retardant inorganic filler, 5-10g of antibacterial modified filler and 1-5g of silane coupling agent KH-550, heat to 50°C, stir and react to obtain the polyurethane A component.
[0007] Furthermore, the vacuum degree of vacuuming in step 1 and step 2 is 0.095 MPa, the stirring speed of the mixed stirring in step 2 is 500-600 r / min, the operation method of strong stirring in step 2 is stirring at a stirring speed of 800-1000 r / min for 1 hour, and the operation method of stirring reaction in step 3 is stirring at a stirring speed of 300-500 r / min for 1 hour.
[0008] Furthermore, the preparation method of the flame retardant inorganic filler in step 3 is: Aluminum hydroxide, magnesium hydroxide and zinc borate are weighed and mixed in a weight ratio of 3:2:1, and stirred at a stirring speed of 400-500 r / min for 10 minutes to obtain a flame retardant inorganic filler.
[0009] Furthermore, the preparation method of the antibacterial modified filler in step 3 is: Tetradecyltrimethylammonium chloride, hexadecyldimethylammonium bromide, octadecyldimethylbenzylammonium bromide and dioctyldimethylammonium chloride are weighed in equal weight ratios and mixed, and stirred at a stirring speed of 300 to 400 r / min for 10 minutes to obtain an antibacterial modified filler.
[0010] Furthermore, the preparation method of the polyurethane B component is: Weigh 20-30g of castor oil into a flask and heat it to 120°C. Vacuum dehydration is carried out under stirring for 2h. Then, pour it into a stirring kettle and cool it to 70°C. Add 80-90g of polymethylene polyphenyl polyisocyanate and heat it to 80°C. Stir and mix to obtain the polyurethane B component.
[0011] Furthermore, in the preparation method of the polyurethane component B, the vacuum degree of the vacuum pumping is 0.095 MPa, the stirring speed of the stirring condition is 300 r / min, and the stirring and mixing operation method is stirring at a stirring speed of 200 r / min for 2 hours.
[0012] Furthermore, the preparation method of the property-enhancing component A is: Calcium oxide, ultraviolet absorber and antioxidant 1010 were weighed and mixed in equal weight ratios, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component A.
[0013] Furthermore, the preparation method of the property-enhancing component B is: Antioxidant 3114 and carbodiimide were weighed and mixed in equal weight ratio, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component B.
[0014] A method for preparing a high-stability multi-element hybrid structural adhesive for new energy lithium batteries, the preparation method comprising: S1. Add 1 to 2 parts by weight of the property-enhancing component A to 45 to 60 parts by weight of the polyurethane component A, and stir at a stirring speed of 200 r / min for 5 minutes to obtain the resultant product, which is recorded as the component A; S2, adding 0.3-0.5 parts by weight of the property-enhancing component B to 10-15 parts by weight of the polyurethane component B, stirring at a stirring speed of 200 r / min for 5 minutes, and recording the result as the component B; S3. Component A and component B are mixed and 0.3-0.5 parts by weight of dibutyltin dilaurate are added, and the mixture is stirred at a stirring speed of 500 r / min for 10 minutes to obtain a high-stability multi-component hybrid structural adhesive for new energy lithium batteries.
[0015] The present invention provides a high-stability multi-element hybrid structural adhesive for new energy lithium batteries and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention realizes multi-hybridization by carefully designing polyurethane component A and polyurethane component B, combined with the addition of property-enhancing component A and property-enhancing component B, which can significantly improve the stability and durability of the structural adhesive. This structural design helps to maintain long-term bonding strength and sealing performance in new energy lithium batteries, thereby improving the overall stability and safety of the battery.
[0016] 2. In the preparation process of the polyurethane component A, the present invention adds a flame retardant plasticizer, a flame retardant inorganic filler and an antibacterial modified filler. The addition of these additives can not only improve the flame retardant properties of the structural adhesive, enabling it to maintain good stability under high temperature or fire conditions, but also give the structural adhesive a certain antibacterial ability, which helps to extend the service life and safety of new energy lithium batteries.
[0017] 3. The addition of the property-enhancing component A and the property-enhancing component B in the present invention can further enhance the environmental adaptability of the structural adhesive. The introduction of additives such as calcium oxide, ultraviolet absorbers and antioxidants can improve the weather resistance and antioxidant properties of the structural adhesive, so that it can maintain stable performance in harsh environments. Moreover, the entire preparation process is relatively simple and easy to control, and the required raw materials and equipment are all conventional materials, which can reduce production costs and preparation difficulty. At the same time, the preparation steps are clear and definite, which is convenient for industrial production and promotion. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The present invention will be further described below in conjunction with the embodiments.
[0020] The sources of some components in the embodiments and comparative examples are as follows: Castor oil, industrial grade, Shandong Weifang Zhenghua Chemical Co., Ltd.; Polyester diol, hydroxyl value 20~500mg / g, industrial grade, Shandong Bluestar Dongda Chemical Co., Ltd.; Polyether polyol, industrial grade, Sinopec Shanghai Gaoqiao Petrochemical Company; Diphenylmethane diisocyanate, technical grade, Huntsman Chemical Co., Ltd.; Trimethylolpropane, industrial grade, Shanghai Hersbit Chemical Co., Ltd.; Fumed silica, technical grade, Wacker Chemie Co., Ltd.; Calcium carbonate powder, 800 mesh, Shanghai Fengchen Powder Material Co., Ltd.; Flame retardant plasticizer, trioctyl phosphate, model FR-CDP, Dongguan Xingyuan Chemical Co., Ltd.; Silane coupling agent KH-550, industrial grade, Shanghai Enchang Industry and Trade Co., Ltd.; Aluminum hydroxide, industrial grade, Jinan Jiuding New Materials Industry Co., Ltd.; Magnesium hydroxide, industrial grade, Jinan Jiuding New Materials Industry Co., Ltd.; Zinc borate, industrial grade, Jinan Jiuding New Materials Industry Co., Ltd.; Tetradecyltrimethylammonium chloride, industrial grade, Jiangsu Runfeng Synthetic Technology Co., Ltd.; Hexadecyl dimethyl ammonium bromide, industrial grade, Jiangsu Pulex Biotechnology Co., Ltd.; Octadecyl dimethyl benzyl ammonium bromide, industrial grade, Xiamen Pioneer Technology Co., Ltd.; Dioctyldimethylammonium chloride, industrial grade, Jinan Quanxing New Materials Co., Ltd.; Polymethylene polyphenyl polyisocyanate, industrial grade, Yantai Wanhua Polyurethane Co., Ltd.; Calcium oxide, industrial grade, Tianjin Biboyuan Technology Development Co., Ltd.; UV absorber, industrial grade, model UV-234, Dongguan Xingyuan Chemical Co., Ltd.; Antioxidant 1010, industrial grade, Jiangsu Xinluda Polymer Materials Co., Ltd.; Antioxidant 3114, industrial grade, Nanjing Milan Chemical Co., Ltd.; Carbodiimide, industrial grade, Suzhou Keshengtong New Material Technology; Dibutyltin dilaurate, industrial grade, Shanghai Lingfeng Chemical Reagent Co., Ltd.
[0021] Embodiment 1: The high-stability multi-component hybrid structural adhesive for new energy lithium batteries of this embodiment is composed of the following components: polyurethane component A, polyurethane component B, enhanced component A, enhanced component B and dibutyltin dilaurate; The polyurethane component A is a hydroxyl-terminated prepolymer prepared with castor oil, polyester diol, polyether polyol, diphenylmethane diisocyanate and trimethylolpropane as main raw materials; The preparation steps of polyurethane A component are: Step 1, weigh 50g of castor oil, 100g of polyester diol and 50g of polyether polyol into a flask, and dehydrate them under vacuum at a temperature of 120°C and a vacuum degree of 0.095MPa for 2h, and the obtained mixture is recorded as a mixed component; Step 2, the mixed components were cooled to 60°C and put into a stirring tank, then 100g of diphenylmethane diisocyanate was added and the temperature was raised to 80°C and mixed at a stirring speed of 500r / min for 2h, then 10g of trimethylolpropane, 1g of fumed silica and 20g of calcium carbonate powder were added, stirred at a stirring speed of 800r / min for 1h, then the temperature was raised to 120°C and vacuumed and dehydrated at a vacuum degree of 0.095MPa for 2h, and the obtained was recorded as the reaction component; Step 3: After cooling the reaction components to 40°C, add 20g of flame retardant plasticizer, 30g of flame retardant inorganic filler, 5g of antibacterial modified filler and 1g of silane coupling agent KH-550, heat to 50°C and stir at a stirring speed of 300r / min for 1h to obtain polyurethane component A.
[0022] The preparation method of the flame retardant inorganic filler in step 3 is: Aluminum hydroxide, magnesium hydroxide and zinc borate were weighed and mixed in a weight ratio of 3:2:1, and stirred at a stirring speed of 400 r / min for 10 minutes to obtain a flame retardant inorganic filler.
[0023] The preparation method of the antibacterial modified filler in step 3 is: Tetradecyltrimethylammonium chloride, hexadecyldimethylammonium bromide, octadecyldimethylbenzylammonium bromide and dioctyldimethylammonium chloride were weighed and mixed in equal weight ratios, and stirred at a stirring speed of 300 r / min for 10 minutes to obtain an antibacterial modified filler.
[0024] The polyurethane B component is an isocyanate-terminated prepolymer prepared with castor oil and polymethylene polyphenyl polyisocyanate as main raw materials.
[0025] The preparation method of polyurethane component B is as follows: Weigh 20 g of castor oil into a flask and heat it to 120°C. Dehydrate it at a vacuum degree of 0.095 MPa for 2 h at a stirring speed of 300 r / min. Then pour it into a stirring kettle and cool it to 70°C. Add 80 g of polymethylene polyphenyl polyisocyanate and raise the temperature to 80°C. Stir at a stirring speed of 200 r / min for 2 h to obtain the polyurethane B component.
[0026] The preparation method of the enhanced component A is as follows: Calcium oxide, ultraviolet absorber and antioxidant 1010 were weighed and mixed in equal weight ratios, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component A.
[0027] The preparation method of the property-enhancing component B is as follows: Antioxidant 3114 and carbodiimide were weighed and mixed in equal weight ratio, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component B.
[0028] A method for preparing a high-stability multi-element hybrid structural adhesive for new energy lithium batteries, the preparation method comprising: S1. Add 1 part by weight of the property-enhancing component A to 45 parts by weight of the polyurethane component A, and stir at a stirring speed of 200 r / min for 5 minutes to obtain the resultant product, which is recorded as component A; S2, adding 0.3 parts by weight of the property-enhancing component B to 10 parts by weight of the polyurethane component B, stirring at a stirring speed of 200 r / min for 5 minutes, and recording the result as the component B; S3. Component A and component B are mixed and 0.3 parts by weight of dibutyltin dilaurate is added, and the mixture is stirred at a stirring speed of 500 r / min for 10 minutes to obtain a high-stability multi-component hybrid structural adhesive for new energy lithium batteries.
[0029] Embodiment 2: The high-stability multi-component hybrid structural adhesive for new energy lithium batteries of this embodiment is composed of the following components: polyurethane component A, polyurethane component B, enhanced component A, enhanced component B and dibutyltin dilaurate; The polyurethane component A is a hydroxyl-terminated prepolymer prepared with castor oil, polyester diol, polyether polyol, diphenylmethane diisocyanate and trimethylolpropane as main raw materials; The preparation steps of polyurethane A component are: Step 1, weigh 60g of castor oil, 120g of polyester diol and 60g of polyether polyol into a flask, and dehydrate them under vacuum at a temperature of 120°C and a vacuum degree of 0.095MPa for 2h, and the obtained mixture is recorded as a mixed component; Step 2, the mixed components were cooled to 60°C and put into a stirring kettle, then 130g of diphenylmethane diisocyanate was added and the temperature was raised to 80°C and mixed at a stirring speed of 600r / min for 2h, then 20g of trimethylolpropane, 5g of fumed silica and 40g of calcium carbonate powder were added, stirred at a stirring speed of 1000r / min for 1h, then the temperature was raised to 120°C and vacuumed and dehydrated at a vacuum degree of 0.095MPa for 2h, and the obtained was recorded as the reaction component; Step 3: After cooling the reaction components to 40°C, add 40g of flame retardant plasticizer, 50g of flame retardant inorganic filler, 10g of antibacterial modified filler and 5g of silane coupling agent KH-550, heat to 50°C and stir at a stirring speed of 500r / min for 1h to obtain polyurethane component A.
[0030] The preparation method of the flame retardant inorganic filler in step 3 is: Aluminum hydroxide, magnesium hydroxide and zinc borate were weighed and mixed in a weight ratio of 3:2:1, and stirred at a stirring speed of 500 r / min for 10 minutes to obtain a flame retardant inorganic filler.
[0031] The preparation method of the antibacterial modified filler in step 3 is: Tetradecyltrimethylammonium chloride, hexadecyldimethylammonium bromide, octadecyldimethylbenzylammonium bromide and dioctyldimethylammonium chloride were weighed and mixed in equal weight ratios, and stirred at a stirring speed of 400 r / min for 10 minutes to obtain an antibacterial modified filler.
[0032] The polyurethane B component is an isocyanate-terminated prepolymer prepared with castor oil and polymethylene polyphenyl polyisocyanate as main raw materials.
[0033] The preparation method of polyurethane component B is as follows: Weigh 30 g of castor oil into a flask and heat it to 120°C. Dehydrate it at a vacuum degree of 0.095 MPa for 2 h at a stirring speed of 300 r / min. Then pour it into a stirring kettle and cool it to 70°C. Add 90 g of polymethylene polyphenyl polyisocyanate and raise the temperature to 80°C. Stir at a stirring speed of 200 r / min for 2 h to obtain the polyurethane B component.
[0034] The preparation method of the enhanced component A is as follows: Calcium oxide, ultraviolet absorber and antioxidant 1010 were weighed and mixed in equal weight ratios, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component A.
[0035] The preparation method of the property-enhancing component B is as follows: Antioxidant 3114 and carbodiimide were weighed and mixed in equal weight ratio, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component B.
[0036] A method for preparing a high-stability multi-element hybrid structural adhesive for new energy lithium batteries, the preparation method comprising: S1, add 2 parts by weight of the property-enhancing component A to 60 parts by weight of the polyurethane component A, and stir at a stirring speed of 200 r / min for 5 minutes to obtain the resultant product, which is recorded as component A; S2, adding 0.5 parts by weight of the property-enhancing component B to 15 parts by weight of the polyurethane component B, stirring at a stirring speed of 200 r / min for 5 minutes, and recording the result as the component B; S3. Component A and component B are mixed and 0.5 parts by weight of dibutyltin dilaurate are added, and the mixture is stirred at a stirring speed of 500 r / min for 10 minutes to obtain a high-stability multi-component hybrid structural adhesive for new energy lithium batteries.
[0037] Embodiment 3: The high-stability multi-component hybrid structural adhesive for new energy lithium batteries of this embodiment is composed of the following components: polyurethane component A, polyurethane component B, enhanced component A, enhanced component B and dibutyltin dilaurate; The polyurethane component A is a hydroxyl-terminated prepolymer prepared with castor oil, polyester diol, polyether polyol, diphenylmethane diisocyanate and trimethylolpropane as main raw materials; The preparation steps of polyurethane A component are: Step 1, weigh 55g of castor oil, 110g of polyester diol and 55g of polyether polyol into a flask, and dehydrate them under vacuum at a temperature of 120°C and a vacuum degree of 0.095MPa for 2h, and the obtained mixture is recorded as a mixed component; Step 2, the mixed components were cooled to 60°C and put into a stirring kettle, then 120g of diphenylmethane diisocyanate was added and the temperature was raised to 80°C and mixed at a stirring speed of 600r / min for 2h, then 15g of trimethylolpropane, 3g of fumed silica and 30g of calcium carbonate powder were added, stirred at a stirring speed of 900r / min for 1h, then the temperature was raised to 120°C and vacuumed and dehydrated at a vacuum degree of 0.095MPa for 2h, and the obtained was recorded as the reaction component; Step 3: After cooling the reaction components to 40°C, add 30g of flame retardant plasticizer, 40g of flame retardant inorganic filler, 8g of antibacterial modified filler and 3g of silane coupling agent KH-550, heat to 50°C and stir at a stirring speed of 400r / min for 1h to obtain polyurethane component A.
[0038] The preparation method of the flame retardant inorganic filler in step 3 is: Aluminum hydroxide, magnesium hydroxide and zinc borate were weighed and mixed in a weight ratio of 3:2:1, and stirred at a stirring speed of 500 r / min for 10 minutes to obtain a flame retardant inorganic filler.
[0039] The preparation method of the antibacterial modified filler in step 3 is: Tetradecyltrimethylammonium chloride, hexadecyldimethylammonium bromide, octadecyldimethylbenzylammonium bromide and dioctyldimethylammonium chloride were weighed and mixed in equal weight ratios, and stirred at a stirring speed of 400 r / min for 10 minutes to obtain an antibacterial modified filler.
[0040] The polyurethane B component is an isocyanate-terminated prepolymer prepared with castor oil and polymethylene polyphenyl polyisocyanate as main raw materials.
[0041] The preparation method of polyurethane component B is as follows: Weigh 25 g of castor oil into a flask and heat it to 120°C. Dehydrate it at a vacuum degree of 0.095 MPa for 2 h at a stirring speed of 300 r / min. Then pour it into a stirring kettle and cool it to 70°C. Add 85 g of polymethylene polyphenyl polyisocyanate and raise the temperature to 80°C. Stir at a stirring speed of 200 r / min for 2 h to obtain the polyurethane B component.
[0042] The preparation method of the enhanced component A is as follows: Calcium oxide, ultraviolet absorber and antioxidant 1010 were weighed and mixed in equal weight ratios, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component A.
[0043] The preparation method of the property-enhancing component B is as follows: Antioxidant 3114 and carbodiimide were weighed and mixed in equal weight ratio, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component B.
[0044] A method for preparing a high-stability multi-element hybrid structural adhesive for new energy lithium batteries, the preparation method comprising: S1. Add 2 parts by weight of the property-enhancing component A to 53 parts by weight of the polyurethane component A, and stir at a stirring speed of 200 r / min for 5 minutes to obtain the resultant product, which is referred to as component A. S2, adding 0.4 parts by weight of the property-enhancing component B to 13 parts by weight of the polyurethane component B, stirring at a stirring speed of 200 r / min for 5 minutes, and recording the result as the component B; S3. Component A and component B are mixed and 0.4 parts by weight of dibutyltin dilaurate are added, and the mixture is stirred at a stirring speed of 500 r / min for 10 minutes to obtain a high-stability multi-component hybrid structural adhesive for new energy lithium batteries.
[0045] Comparative Example 1: The high-stability multi-element hybrid structural adhesive for new energy lithium batteries and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the flame-retardant inorganic filler in Example 1 is not added to this comparative example 1.
[0046] Comparative Example 2: The high-stability multi-component hybrid structural adhesive for new energy lithium batteries and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that the property-enhancing component A in Example 1 is not added to this comparative example 2.
[0047] Comparative Example 3: The high-stability multi-component hybrid structural adhesive for new energy lithium batteries and its preparation method provided in this comparative example are roughly the same as those in Example 1, with the main difference being that the property-enhancing component B in Example 1 is not added to this comparative example 3.
[0048] Performance Test: The high-stability multi-element hybrid structural adhesives for new energy lithium batteries prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. Then, the performances of Examples 1-3 and Comparative Examples 1-3 are tested. The specific testing methods and test items are as follows: 1. The tensile strength of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T528-2009, and the obtained data are recorded in Table 1; 2. The shear strength of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T7124-1986, and the obtained data are recorded in Table 1; 3. The limiting oxygen index of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T 2406.2-2009, and the obtained data are recorded in Table 1; 4. The limiting oxygen index of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GJB 446-1988, and the obtained data are recorded in Table 1; Table 1: Performance test data of multi-hybrid structural adhesive Tensile strength MPa Shear strength MPa Limiting oxygen index% Peel strength N / cm Example 1 11.98 13.11 31.65 43.65 Example 2 11.96 13.16 30.98 42.21 Example 3 12.07 12.98 30.67 43.17 Comparative Example 1 10.98 11.98 24.65 41.69 Comparative Example 2 9.98 11.56 23.79 41.39 Comparative Example 3 10.21 11.21 24.15 42.16 It can be seen from the data in the above table that the mechanical properties and flame retardant properties of the high-stability multi-component hybrid structural adhesive for new energy lithium batteries in Examples 1-3 are better than those in Comparative Examples 1-3, indicating that adding flame-retardant inorganic fillers, enhancing components A and enhancing components B in the preparation of high-stability multi-component hybrid structural adhesive for new energy lithium batteries can improve the performance.
[0049] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. High stability multi-component hybrid structural adhesive for new energy lithium batteries, characterized in that: The high-stability multi-component hybrid structural adhesive for new energy lithium batteries is composed of the following components: polyurethane component A, polyurethane component B, enhanced component A, enhanced component B and dibutyltin dilaurate; The polyurethane component A is a hydroxyl-terminated prepolymer prepared with castor oil, polyester diol, polyether polyol, diphenylmethane diisocyanate and trimethylolpropane as main raw materials; The polyurethane B component is an isocyanate-terminated prepolymer prepared with castor oil and polymethylene polyphenyl polyisocyanate as main raw materials.
2. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The preparation steps of the polyurethane A component are: Step 1, weigh 50-60g of castor oil, 100-120g of polyester diol and 50-60g of polyether polyol into a flask, and dehydrate under vacuum at a temperature of 120°C for 2h, and the obtained mixture is recorded as a mixed component; Step 2, cool the mixed components to 60°C and put them into a stirring kettle, then add 100-130g of diphenylmethane diisocyanate and heat to 80°C and mix and stir for 2h, then add 10-20g of trimethylolpropane, 1-5g of fumed silica and 20-40g of calcium carbonate powder, stir vigorously and evenly, then heat to 120°C and vacuum dehydrate for 2h, the result is recorded as the reaction component; Step 3: After cooling the reaction components to 40°C, add 20-40g of flame retardant plasticizer, 30-50g of flame retardant inorganic filler, 5-10g of antibacterial modified filler and 1-5g of silane coupling agent KH-550, heat to 50°C, stir and react to obtain the polyurethane A component.
3. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 2, characterized in that: The vacuum degree of the vacuum extraction in step 1 and step 2 is 0.095 MPa, the stirring speed of the mixed stirring in step 2 is 500-600 r / min, the operation method of the strong stirring in step 2 is stirring at a stirring speed of 800-1000 r / min for 1 hour, and the operation method of the stirring reaction in step 3 is stirring at a stirring speed of 300-500 r / min for 1 hour.
4. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 2, characterized in that: The preparation method of the flame retardant inorganic filler in step 3 is: Aluminum hydroxide, magnesium hydroxide and zinc borate are weighed and mixed in a weight ratio of 3:2:1, and stirred at a stirring speed of 400-500 r / min for 10 minutes to obtain a flame retardant inorganic filler.
5. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 2, characterized in that: The preparation method of the antibacterial modified filler in step 3 is: Tetradecyltrimethylammonium chloride, hexadecyldimethylammonium bromide, octadecyldimethylbenzylammonium bromide and dioctyldimethylammonium chloride are weighed in equal weight ratios and mixed, and stirred at a stirring speed of 300 to 400 r / min for 10 minutes to obtain an antibacterial modified filler.
6. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The preparation method of the polyurethane B component is: Weigh 20-30g of castor oil into a flask and heat it to 120°C. Vacuum dehydration is carried out under stirring for 2h. Then, pour it into a stirring kettle and cool it to 70°C. Add 80-90g of polymethylene polyphenyl polyisocyanate and heat it to 80°C. Stir and mix to obtain the polyurethane B component.
7. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 6, characterized in that: In the preparation method of the polyurethane component B, the vacuum degree of the vacuum pumping is 0.095 MPa, the stirring speed of the stirring condition is 300 r / min, and the stirring and mixing operation method is to stir at a stirring speed of 200 r / min for 2 hours.
8. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The preparation method of the property-enhancing component A is as follows: Calcium oxide, ultraviolet absorber and antioxidant 1010 were weighed and mixed in equal weight ratios, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component A.
9. The high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to claim 1, characterized in that: The preparation method of the property-enhancing B component is: Antioxidant 3114 and carbodiimide were weighed and mixed in equal weight ratio, poured into a ball mill and milled for 5 minutes to obtain the property-enhancing component B.
10. The method for preparing a high-stability multi-component hybrid structural adhesive for new energy lithium batteries according to any one of claims 1 to 9, characterized in that: The preparation method is: S1. Add 1 to 2 parts by weight of the property-enhancing component A to 45 to 60 parts by weight of the polyurethane component A, and stir at a stirring speed of 200 r / min for 5 minutes to obtain the resultant product, which is recorded as the component A; S2, adding 0.3-0.5 parts by weight of the property-enhancing component B to 10-15 parts by weight of the polyurethane component B, stirring at a stirring speed of 200 r / min for 5 minutes, and recording the result as the component B; S3. Component A and component B are mixed and 0.3-0.5 parts by weight of dibutyltin dilaurate are added, and the mixture is stirred at a stirring speed of 500 r / min for 10 minutes to obtain a high-stability multi-component hybrid structural adhesive for new energy lithium batteries.
Citation Information
Patent Citations
High-temperature-cooking-resistant solvent-free two-component polyurethane adhesive and preparation method thereof
CN115109556A
Compound disinfection and sterilization method
CN116349679A
High-hardness inorganic-organic hybrid resin and preparation process thereof
CN116656086A
Vegetable oil-based flame-retardant bi-component polyurethane adhesive and preparation method thereof
CN117106406A
Detachable polyurethane structural adhesive with flame retardant property and preparation method thereof
CN117903743A